A new species of Rhodambulyx Mell, 1939 (Lepidoptera: Sphingidae) from Southwest Chongqing, China - Xu, Zhen-Bang; Melichar, Tomáš; He, Ji-Bai; Zhang, Chao; Zhang, Xin-Yu; Feng, du; Hu, Shao-Ji (Zootaxa, 2022)
A new species of the genus Rhodambulyx Mell, 1939, Rhodambulyx xinyuae sp. nov., is described from Simianshan Nature Reserve in Southwest Chongqing, China. This species is similar to R. davidi Mell, 1939 and R. kitchingi Brechlin, 2015 in habitus, but can be distinguished by a different wing pattern, male genitalia structure and DNA barcode sequence. In addition, Rhodambulyx namvui Eitschberger & Nguyen, 2017 is removed from synonymy with R. kitchingi and synonymized instead with R. davidi, although whether it would be better treated as a subspecies of R. davidi requires further investigation.